The Effect of Financial Risk and Enterprise Internal Management on Enterprise Performance of Automotive and Automotive Part Industry in Thailand - Thirapanmethee, Piya; Pichayasupakoon, Tiyadah; Bootchai, Nilubon (วารสารการจัดการธุรกิจ มหาวิทยาลัยบูรพา, 2022)
The main objective of this study is to examine factors affecting financial risk management and enterprise internal management on enterprise performance of automotive and automotive parts industry in Thailand using empirical data. The sample was chosen from companies in automotive parts manufacturing industry in Thailand. The questionnaires were distributed to 334 respondents. The statistics were descriptive statistics, confirmatory factor analysis and structural equation model. The results show that the conceptual model aligned with the empirical data. (c2=121.331, p = .279, c2/df = 1.074, GFI = 0.962, AGFI = 0.936, CFI = 0.998 RMSEA = 0.015) The findings indicated that financial risk management had positive impacts on enterprise internal management at significance level 0.01. Enterprise internal management had positive impacts on enterprise performance at significance level = 0.01 Furthermore, the outcome showed that financial risk management had direct and indirect impacts on enterprise performance at significance level = 0.01. which confirmed the relationship of factors that influenced enterprise performance in Thailand’s automotive industry.